2018
DOI: 10.1123/jsep.2017-0360
|View full text |Cite
|
Sign up to set email alerts
|

In the Zone: An Exploration of Personal Characteristics Underlying Affective Responses to Heavy Exercise

Abstract: Positive affective responses to exercise have been linked with longer term adherence. The Dual-Mode Model indicates that affective responses during heavy exercise (between the ventilatory threshold and the respiratory compensation point) are subject to interindividual variability (zone of response variability). Participants (N = 48) completed measures to assess personal characteristics prior to a graded exercise test (GXT). Responses to the Feeling Scale were recorded during the GXT and subsequently used to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Specifically, Ekkekakis et al (2005) introduced the constructs of exercise intensity preference, defined as the predisposition to choose a particular level of exercise intensity when given the opportunity, and exercise intensity tolerance, defined as the ability to tolerate an imposed level of intensity that is unpleasant or uncomfortable. These individualdifference dispositions, assessed by the Preference for and Tolerance of the Intensity of Exercise Questionnaire (PRETIE-Q), have been found to account for significant portions of the variance in affective valence responses to exercise (e.g., Box & Petruzzello, 2020;Jones et al, 2018), and may have implications for the affectadherence relationship (Faria et al, 2021;Teixeira et al, 2022). Given the present finding of escalating variance in affective valence responses to increasing levels of resistance, it is reasonable to suggest that further investigations of the relation of affective valence ratings with intensity-preference and, especially, intensity-tolerance are warranted.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Specifically, Ekkekakis et al (2005) introduced the constructs of exercise intensity preference, defined as the predisposition to choose a particular level of exercise intensity when given the opportunity, and exercise intensity tolerance, defined as the ability to tolerate an imposed level of intensity that is unpleasant or uncomfortable. These individualdifference dispositions, assessed by the Preference for and Tolerance of the Intensity of Exercise Questionnaire (PRETIE-Q), have been found to account for significant portions of the variance in affective valence responses to exercise (e.g., Box & Petruzzello, 2020;Jones et al, 2018), and may have implications for the affectadherence relationship (Faria et al, 2021;Teixeira et al, 2022). Given the present finding of escalating variance in affective valence responses to increasing levels of resistance, it is reasonable to suggest that further investigations of the relation of affective valence ratings with intensity-preference and, especially, intensity-tolerance are warranted.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…They have shown that preference (i.e., a predisposition to select a particular level of intensity) and tolerance (i.e., a trait that influences one's ability to continue exercising at a defined level of intensity) are linked to individual's affective response to exercise and fitness performance (Ekkekakis et al, 2005(Ekkekakis et al, , 2006(Ekkekakis et al, , 2007Hall et al, 2014;Jones et al, 2018). Some of these studies have shown that preference and tolerance were positively associated with total leisure-time exercise (Ekkekakis et al, 2008), exercise frequency (Ekkekakis et al, 2007;Teixeira et al, 2021), and could predict affective responses in high intensity exercise protocols (Jones et al, 2018;Box and Petruzzello, 2020). However, and despite some studies providing evidence in favor of an intensity-guided exercise prescription aiming to promote distinct and beneficial behavioral, cognitive and emotional outcomes, a large gap still exists in other contexts, populations, and variables of interest.…”
Section: The Role (And Promotion) Of Enjoyment In Exercisementioning
confidence: 99%
“…High Intensity Training (HIT) is known to be beneficial for cognitive function in children, although the impact differs between individuals [35]. Recent evidence in adults shows that preference for higher intensity activity is predictive of affective response [36]-i.e. those who feel better after intense PA are more likely to want to do intense activity than those who do not feel better.…”
Section: Relation To Previous Literaturementioning
confidence: 99%